(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2018)
Objective: To analyze the national and international scientific productions developed by nurses about the care of the person with gastrostomy. Method: Integrative review including articles published by nursing, from 2005 to 2015, in national and international journals and that answer the following guiding question: What has been produced by nursing about the care of the person with gastrostomy? Articles in Portuguese, Spanish and English, available totality, were established as inclusion criteria. The databases used were: PUBMED, Nursing Database (BDENF), Scopus and Web of Science. The Boolean operators AND/OR were used as well as the descriptors selected in the Descriptors in Health Sciences: “gastrostomy” AND “family nursing”, from the integrated method in Portuguese and English. Results: Eight articles answered the guiding question. It was verifi ed that in the multidisciplinary team the role of the nurse is fundamental, both in the hospital and at home, to guarantee the care of the child, the adult and the elderly with gastrostomy. Conclusion: In planning care, nurses should have technical and scientifi c knowledge, better explore their clinical role and understand the needs of the person with gastrostomy and it family. The studies highlighted the scarcity of scientifi c productions about the theme.